2011
DOI: 10.1210/en.2011-1147
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA378 (miR-378) Regulates Ovarian Estradiol Production by Targeting Aromatase

Abstract: Estradiol is a steroid hormone that not only plays an important role in ovarian follicular development but also is associated with many reproductive disorders. Owing to the importance of aromatase in the production of estradiol, the regulation of aromatase gene expression at the transcriptional level has been an extensive area of study for over two decades. However, its regulation at the posttranscriptional level has remained unclear. Here, we show that micro-RNA378 (miR-378) is spatiotemporally expressed in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 55 publications
5
130
1
2
Order By: Relevance
“…Thus, miRNA-145 may not necessarily lead to the modulation of specific predicted functions or targets, but it has been reported to function as a regulator of cell proliferation and as a tumor suppressor (20,69,79,84). A number of studies have attempted to identify and characterize miRNAs in adrenal and gonadal tissues and cells (18,24,45,47,48,50,54,63,68,80,81,83), but information about their potential targets or hormonal regulation is generally lacking except in a few instances. For example, miRNA-378 has been reported to regulate estradiol production in porcine granulosa cells by targeting aromatase (47).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miRNA-145 may not necessarily lead to the modulation of specific predicted functions or targets, but it has been reported to function as a regulator of cell proliferation and as a tumor suppressor (20,69,79,84). A number of studies have attempted to identify and characterize miRNAs in adrenal and gonadal tissues and cells (18,24,45,47,48,50,54,63,68,80,81,83), but information about their potential targets or hormonal regulation is generally lacking except in a few instances. For example, miRNA-378 has been reported to regulate estradiol production in porcine granulosa cells by targeting aromatase (47).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already reported effects of specific miRNAs on different aspects of granulosa cell function , including steroidogenesis (Yao et al 2010, Xu et al 2011, Yin et al 2012, Dai et al 2013, proliferation (Yao et al 2010, Yan et al 2012, Dai et al 2013, survival (Carletti et al 2010, Yang et al 2012, terminal differentiation (Kitahara et al 2013), and cumulus expansion (Yao et al 2014). With a few exceptions (Carletti et al 2010, Kitahara et al 2013, most evidence on follicular roles of miRNAs has been obtained using cultured cells, particularly rodent cells, and in some cases actual changes in the expression of these miRNAs during follicle development have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies identified novel and ovarian-specific miRNA species, comparisons across different developmental stages were not performed. Separate studies identified hormoneresponsive miRNAs in the ovary and proposed different roles for some of those miRNAs including mediation of granulosa cell responses to transforming growth factor b1 (TGFb1) in pre-antral follicles (Yao et al 2010a), oestradiol (E 2 ) production (Xu et al 2011), prevention of early granulosa cell differentiation (Lei et al 2010), promotion of granulosa cell survival during ovulation (Carletti et al 2010), inhibition of anti-angiogenic factor expression during luteogenesis (Otsuka et al 2008) and ovarian aging (da Silveira et al 2012). It has not yet been established whether these proposed functions are conserved in large animal species and humans.…”
Section: Introductionmentioning
confidence: 99%